The adaptive geometrey {i.e. geometry} of savanna trees : a comparative study of the architecture and life history of Acacia karroo Hayne. in savanna, forest, and arid karoo shrubland environments - Archibald, Sally (Department of Biological Sciences, 2017)
Various morphological and life history attributes of Acacia karroo Hayne. were investigated in five populations from three environments in South Africa: forest (Cape Vidal, Natal), arid shrubland (Prince Albert, karoo) and savanna (Hluhluwe-Umfolozi Game reserve and ltala Game reserve, Natal). I aimed to elucidate on the distinctive characteristics required for trees to survive in savannas. The combination of frequent fires and intense herbivory in savanna environments creates a disturbance regime not encountered by trees in other situations and it was expected that A.karroo would display specific adaptations of growth form, life history, and reproductive ecology - adaptations which would reflect the strong selective pressure imposed by fire and herbivory on juvenile savanna trees to grow above flame height and browse limit in order to recruit into the mature canopy. A. karroo in savannas was found to have an unbranched, vertical growth form, and is thus maximising height gain. Reproduction was delayed until the trees were above the reach of flames and herbivores. Savanna A.karroo trees had fewer, smaller spines than trees in the other two environments, even though spines are generally considered to be effective in defense against mammalian herbivores. It is therefore suggested that a combination of low 'apparency' to browsers and rapid growth rate is an effective herbivore avoidance strategy in conditions where the need to escape from the fire trap makes a trade-off of growth rate for defensive structures unacceptable. The architecture of mature savanna trees reflects their history of rapid growth in earlier stages and they have smaller canopies, and thus lower reproductive capabilities, than equivalently sized trees in other environments.